Globální paradigma managementu a jeho změna - Mandysová, Ivana (Univerzita Pardubice, 2002)
The move of paradigm is understood as an old principles forfeit followed by creation of new ones. New information from scientific sphere anticipates. Assuming classical old industrial model was partial assignment. New conditions of company environment cause integration of partial assignments into one complex aggregate. Customer determines simultaneously scale of products and secures at the same time customers loyalty. Changes in management are required and they are under way continuously or radically.
Keywords: Management; paradigma; teorie; zákazníci; Integrace